(Re)pensar o uso do tijolo em arquitectura através de fabricação digital - João Vitor Pereira Azevedo (2013)
The paradigmatic change of digital fabrication, present nowadays, incites the architects to incorporate the new acquirements in materials already used and solve ancient construction problems with new techniques. Taking into account the masonry construction and the robotic processes, this essay will experiment new methods of digital fabrication for an organic structure and free-form, through an automatic element. In order to develop the classic procedures of masonry construction. Beginning with research about the techniques used to make masonry and his principal faults, followed by the current approaches of digital fabrication and their applications. Based on these topics and with the integration of the author in a research group of Investigação Jovem da Universidade do Porto (IJUP), processes of parametric and algorithmic computational design (CAD) will be explored, in order to elaborate complex forms as from standard elements and get coordinates in space. Still, with the data obtained, will be explored processes of automatic assembly, with the intention to grab, carry, orient and positioning each brick in physical space.